Competency Standards as a Tool for Human Capital Development : Assessment of Their Development and Introduction into TVET and Certification in Indonesia - World Bank (World Bank, Washington, DC, 2020)
In anticipation of the Industrial Revolution 4.0, the Government of Indonesia has shown a strong commitment to improve the quality of its human capital and, therefore, promote economic growth. Improving human capital will require several actions to improve the education and health outcomes of the population and provide opportunities for lifelong learning that will allow the adult population to receive training to upskill and reskill in line with the labor market changes due to technological progress. A key dimension of the actions to promote labor market readiness of those attending education and training is their labor market relevance: the skills acquired should be demanded by the labor market. Besides this first chapter of introduction, this report has other five chapters. The second chapter presents briefly the methodology of study. The third chapter focuses on main definitions and regulations that guide the process of defining the competences in Indonesia. The fourth chapter discusses the progress that Indonesia has made in the definition of competences as well as the main challenges in their elaboration, the fifth chapter presents how the competences has reached the education system. The sixth chapter presents a summary of the main finding as well as a set of recommendations.